MORBIDITY PATTERN IN ISCHEMIC STROKE PATIENTS AT A TERTIARY CARE HOSPITAL OF SOUTHERN PUNJAB - HASSAN , S; SIDDIQUI , FN; REHMAN , S; SAFDAR , S; IBRAHIM , M; TARIQ , M (Biological and Clinical Sciences Research Journal, 2024)
Medical complications are commonly encountered by neurologists all over the world among ischemic stroke patients. Hence, this study was done to ascertain the burden of such medical complications. Objective: To document the pattern and burden of different medical complications in patients with ischemic stroke at a tertiary care hospital. Methods: This cross-sectional study was conducted at the Department of Neurology, Nishtar Hospital Multan. Stroke patients have undergone relevant investigations like urine tests, blood tests, and ECG for diagnosis of different medical complications such as UTI, shoulder pain, arrhythmia, pneumonia, and hyponatremia. Data was entered and analysed using the computer program SPSS-22. Results: Among these patients, 55.8% were male patients versus 44.2% were females with mean ages of 50.68± 7.18 years. Diabetes was noted in 23.8 %, hypertension was reported in 65.2%, and obesity was noted in 29 (16%). The previous history of stroke was 11.6%, the family history of stroke was 20.4%, and 23.8 % were smokers. Serum sodium level was presented as Mean value of 135.89 ± 1.95 mEq/L, urinary tract infection (UTI) was diagnosed in 48.1%, shoulder pain was 39.8%, pneumonia in 23.8%, arrhythmia 32 % and hyponatremia 28.2%. Conclusion: A high burden of medical complications among ischemic stroke patients was observed, with UTI as the most prevalent complication, which was followed by pain in the shoulder, arrhythmias, pneumonia, and hyponatremia. Our study results emphasise the need for careful monitoring of stroke patients to avoid these complications, which exert extra pressure on healthcare settings and are also associated with significant increases in healthcare-related costs.